Projektirovanie trenirovocnych zadanij v ucebnych programmach dlja DJUSS - Germanov, G. N.; Nikutuschkin, V. G. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2006)
In many respects the overall performance of sports schools depends on the due maintenance of teaching and educational process of young athletes with the program-methodical documents, among which the curriculums in kinds of sports have determining value. Therefore there was a necessity of the further scientific perfection and creative processing of the program documents according to the modern requirements where the substantiation of normative and methodical sections of programs becomes an actual scientific task of the current time.